Comprehensive characterization of switching and conduction losses in high-ratio step-down converters for next-generation electric vehicles - Al-Araji, Zainab Hussam; Almawlawe, Muhanad D. Hashim; Wali, Musa Hadi (Sustainable Engineering and Innovation, 2025)
Sustainable energy has become a critical focus due to the environmental and economic limitations of traditional fossil fuels. One of the most prominent applications in this field is electric vehicles (EVs), which rely on high-voltage DC battery packs (typically 400V or 800V) as their primary energy source. These batteries supply power to AC motors via inverters that convert direct current (DC) to alternating current (AC). Additionally, EVs incorporate DC-DC converter systems to step down the high-voltage DC for auxiliary systems such as infotainment units, control modules, and lighting. The step-down DC-DC converter is composed of various components, including switches (such as MOSFETs or IGBTs) and diodes. These components are subject to different types of losses—namely switching, conduction, and thermal losses—which can significantly impact system efficiency and performance. This article investigates these losses through simulation using the PLECS software across multiple operating scenarios.